Undenatured Type II Collagen Ameliorates Inflammatory Responses and Articular Cartilage Damage in the Rat Model of Osteoarthritis - Orhan, Cemal; Juturu, Vijaya; Sahin, Emre; Tuzcu, Mehmet; Ozercan, Ibrahim Hanifi; Durmus, Ali Said; Sahin, Nurhan; Sahin, Kazim (Frontiers in Veterinary Science, 2021)
Osteoarthritis (OA) is an age-related joint disease that includes gradual disruption of the articular cartilage and the resulting pain. The present study was designed to test the effects of undenatured type II collagen (UCII®) on joint inflammation in the monoiodoacetate (MIA) OA model. We also investigated possible mechanisms underlying these effects. Female Wistar rats were divided into three groups: (i) Control; (ii) MIA-induced rats treated with vehicle; (iii) MIA-induced rats treated with UCII (4 mg/kg BW). OA was induced in rats by intra-articular injection of MIA (1 mg) after seven days of UCII treatment. UCII reduced MIA-induced Kellgren-Lawrence scoring (53.3%, P<0.05). The serum levels of inflammatory cytokines [IL-1β (7.8%), IL-6 (18.0%), TNF-α (25.9%), COMP (16.4%), CRP (32.4%)] were reduced in UCII supplemented group (P<0.0001). In the articular cartilage, UCII inhibited the production of PGE2 (19.6%) and the expression of IL-1β, IL-6, TNF-a, COX-2, MCP-1, NF-κB, MMP-3, RANKL (P<0.001). The COL-1 and OPG levels were increased, and MDA decreased in UCII supplemented rats (P<0.001). UCII could be useful to alleviate joint inflammation and pain in OA joints by reducing the expression of inflammatory mediators.